2018
DOI: 10.32674/jis.v8i3.52
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Social Capital Through International Students’ Involvement in Campus Organizations

Abstract: This study examines campus organization involvement as a mechanism for social capital development. Researchers used analysis of variance (ANOVA) to examine variations in network size, strength, and composition for international students involved in different types of campus organizations. The researchers also examined the relationship of campus organization involvement to international students’ sense of attachment to the university. Students who participated in major-based organizations o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 22 publications
2
16
0
1
Order By: Relevance
“…According to the results of the study, it was recorded that one of the motives for mobility is interesting communication, obviously in a different socio-cultural environment, to be part of the intellectual elite. This confirms the conclusions of experts that studying abroad is not only an opportunity to increase one's human capital, but also social one [22]. In this case, this is naturally associated with the passage of the process of intercultural adaptation, which is consistent with the works of Wang Y., Li T., Noltemeyer A., Wang A., Shaw K. They note the rapid acquisition of sociocultural skills among students studying outside their permanent place of residence, in a different cultural environment, such as Japanese students in New Zealand [23].…”
Section: Discussionsupporting
confidence: 89%
“…According to the results of the study, it was recorded that one of the motives for mobility is interesting communication, obviously in a different socio-cultural environment, to be part of the intellectual elite. This confirms the conclusions of experts that studying abroad is not only an opportunity to increase one's human capital, but also social one [22]. In this case, this is naturally associated with the passage of the process of intercultural adaptation, which is consistent with the works of Wang Y., Li T., Noltemeyer A., Wang A., Shaw K. They note the rapid acquisition of sociocultural skills among students studying outside their permanent place of residence, in a different cultural environment, such as Japanese students in New Zealand [23].…”
Section: Discussionsupporting
confidence: 89%
“…Importantly, campus integration substantially predicts the use of academic support services. Scholars have consistently found that student integration and sense of belonging is directly linked to student success and retention (Tinto, 1987(Tinto, , 2017 and have highlighted the importance of social capital in the utilization of campus resources (Glass & Gesing, 2018;Means & Pyne, 2017). Similarly, we found that studying with peers and communicating with instructors more frequently increased the odds of using academic support services.…”
Section: Discussionsupporting
confidence: 54%
“…Like domestic students, international students can benefit socially from joining student organizations, although they may be more hesitant to do so. Glass and Gesing (2018) found that only 38% of international students studying at a research university in the U.S. had joined an organization on campus, and students from outside Europe tend to be less involved and have fewer host national friends (Glass et al, 2014). Having a faculty or staff mentor instead of a fellow student mentor shows some promise at increasing international student leadership capacity and self-efficacy (Shalka et al, 2019), and better relationships with faculty predict student belonging (Glass et al, 2015).…”
Section: Intercultural Competence: What Work For College Students?mentioning
confidence: 99%